Composition for secondary battery electrode mixture layer, secondary battery electrode, and secondary battery

JP7643342B2Active Publication Date: 2025-03-11TOAGOSEI CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021558323
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-20
Filing Date
2020-11-12
Publication Date
2025-03-11
Estimated Expiration
2040-11-12

AI Technical Summary

Benefits of technology

【0010】 本発明の二次電池電極合剤層用組成物によれば、従来よりも電極合剤層用組成物の固形分濃度が高い場合において、電極スラリーの粘度低減により塗工性を確保しつつ、優れたサイクル特性を発揮する二次電池を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643342000001
    Figure 0007643342000001
  • Figure 0007643342000002
    Figure 0007643342000002
Patent Text Reader

Abstract

The present invention provides a secondary battery electrode compound layer composition that is capable of yielding a secondary battery that exhibits superior cycle properties while ensuring ease of application through reduced electrode slurry viscosity at a higher solids concentration on the part of the electrode compound layer composition than in the prior art. The present invention also provides a secondary battery electrode and a secondary battery obtained by using the composition. The present invention pertains to a secondary battery electrode compound layer composition containing a binder, an active material, and water, the solids concentration of the composition being 40% by mass or higher, wherein: the binder contains a cross-linked polymer comprising a carboxyl group, and a non-cross-linked polymer comprising a structural unit derived from an ethylenically unsaturated carboxylic acid monomer; and the amount used of the non-cross-linked polymer is 7.5 parts by mass to 200 parts by mass, inclusive, per 100 total parts by mass of the cross-linked polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for a secondary battery electrode mixture layer, a secondary battery electrode, and a secondary battery. [Background technology]

[0002] As secondary batteries, various electric storage devices such as nickel-hydrogen secondary batteries, lithium-ion secondary batteries, and electric double layer capacitors have been put to practical use. Electrodes used in these secondary batteries are prepared by coating a composition for forming an electrode mixture layer containing an active material and a binder on a current collector and drying it. For example, in lithium-ion secondary batteries, an aqueous binder containing styrene butadiene rubber (SBR) latex and carboxymethyl cellulose (CMC) is used as the binder used in the negative electrode mixture layer composition. On the other hand, an N-methyl-2-pyrrolidone (NMP) solution of polyvinylidene fluoride (PVDF) is widely used as the binder used in the positive electrode mixture layer.

[0003] As the applications of various secondary batteries expand, there is a tendency for the demand for improved energy density, reliability, and durability to increase. For example, in order to increase the electric capacity of lithium-ion secondary batteries, specifications using silicon-based active materials as negative electrode active materials are becoming more common. However, it is known that silicon-based active materials have a large volume change during charging and discharging, and as they are used repeatedly, peeling or falling off of the electrode mixture layer occurs, resulting in a decrease in the capacity of the battery and a deterioration in cycle characteristics (durability). In order to suppress such defects, it is generally effective to firmly bind the active materials together using a binder (binding property), and studies on improving the binding property of the binder are being conducted in order to improve durability.

[0004] In this context, it has recently been reported that acrylic acid-based polymers are effective as binders for use in negative electrode mixture layers using silicon-based active materials. For example, Patent Document 1 discloses that by using a polymer obtained by crosslinking polyacrylic acid with a specific crosslinking agent as a binder, it is possible to provide an electrode structure without destruction even when an active material containing silicon is used. Patent Document 2 discloses a binder containing a crosslinked polycarboxylate and a linear polycarboxylate, which discloses that an active material layer having high durability against internal stress during volume expansion and contraction during charging and discharging can be obtained. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 065407 [Patent Document 2] International Publication No. 2016 / 051811 Summary of the Invention [Problem to be solved by the invention]

[0006] The binders disclosed in Patent Documents 1 and 2 are both capable of imparting good binding properties, but with improvements in the performance of secondary batteries, there is a demand for electrode mixture layers with high cycle characteristics. Generally, a secondary battery electrode is obtained by applying an electrode mixture layer composition (hereinafter also referred to as "electrode slurry") containing an active material and a binder to the surface of an electrode current collector and drying the applied composition. In this case, it is advantageous to increase the solid content concentration of the electrode mixture layer composition from the viewpoint of increasing the drying efficiency of the electrode slurry and improving the productivity of the electrode, but this makes it difficult to ensure good coatability. In the electrode mixture layer composition described in Patent Document 1, the acrylic acid polymer used as a binder is slightly crosslinked to increase the spreading property in water, thereby improving the binding property, but even a small amount of the acrylic acid polymer increases the viscosity significantly. Therefore, it is difficult to reduce the viscosity of the electrode slurry while increasing the solid content of the electrode mixture layer composition. In addition, the electrode mixture layer composition described in Patent Document 2 uses a crosslinked polycarboxylate and an unneutralized linear polycarboxylic acid in combination as a binder to improve the cycle characteristics (durability) of a secondary battery equipped with an electrode obtained using the composition, but the amount of binder added to the active material is large (Example: total amount of binder is 22 parts by mass per total amount of active material of 100 parts by mass). Therefore, in order to reduce the viscosity of the electrode slurry, it is necessary to increase the amount of water blended, and although the solid content concentration of the electrode mixture layer composition is low (Example: 10% by mass) and the coatability is good, the productivity of the electrode is low.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a composition for a secondary battery electrode mixture layer, which can obtain a secondary battery exhibiting excellent cycle characteristics while ensuring coatability by reducing the viscosity of the electrode slurry when the solid content concentration of the composition for an electrode mixture layer is higher than that of conventional compositions. In addition, an object of the present invention is to provide a secondary battery electrode and a secondary battery obtained by using the composition. [Means for solving the problem]

[0008] As a result of intensive research to solve the above-mentioned problems, the inventors have found that when the solids concentration of a composition for a secondary battery electrode mixture layer containing a binder, an active material and water is high, by containing a specific crosslinked polymer and a specific non-crosslinked polymer and setting the amount of the non-crosslinked polymer used within a specific range relative to 100 parts by mass of the total amount of the crosslinked polymer, it is possible to obtain a secondary battery that exhibits excellent cycle characteristics while ensuring coatability by reducing the viscosity of the electrode slurry, and have completed the present invention.

[0009] The present invention is as follows. [1] A composition for a secondary battery electrode mixture layer comprising a binder, an active material, and water, The solid content of the composition is 40% by mass or more, The binder includes a crosslinked polymer having a carboxyl group and a non-crosslinked polymer having a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, The composition for a secondary battery electrode mixture layer, wherein the amount of the non-crosslinked polymer used is 7.5 parts by mass or more and 200 parts by mass or less per 100 parts by mass of a total amount of the crosslinked polymer. [2] The crosslinked polymer has 50% by mass or more and 100% by mass or less of structural units derived from an ethylenically unsaturated carboxylic acid monomer based on the total structural units thereof, The composition for secondary battery electrode mixture layer according to [1], wherein the non-crosslinked polymer has 50% by mass or more and 100% by mass or less of structural units derived from an ethylenically unsaturated carboxylic acid monomer relative to all structural units thereof. [3] The composition for a secondary battery electrode mixture layer according to [1] or [2], wherein the degree of neutralization of the crosslinked polymer is 70 mol % or more. [4] The composition for secondary battery electrode mixture layer according to any one of [1] to [3], wherein the crosslinked polymer is obtained by using a crosslinkable monomer, and the amount of the crosslinkable monomer used is 0.05 parts by mass or more and 5.0 parts by mass or less per 100 parts by mass of a total amount of non-crosslinkable monomers. [5] The composition for a secondary battery electrode mixture layer according to any one of [1] to [4], wherein the non-crosslinked polymer has a degree of neutralization of 70 mol % or more. [6] The composition for a secondary battery electrode mixture layer according to any one of [1] to [5], wherein the non-crosslinked polymer has a weight average molecular weight of 5,000 or more. [7] The composition for a secondary electrode mixture layer according to any one of [1] to [6], wherein the binder further contains a styrene butadiene rubber (SBR)-based latex and / or carboxymethyl cellulose (CMC). [8] A secondary battery electrode comprising a mixture layer formed on a surface of a current collector from the composition for a secondary battery electrode mixture layer according to any one of [1] to [7]. [9] A secondary battery comprising the secondary battery electrode according to [8]. Effect of the Invention

[0010] According to the secondary battery electrode mixture layer composition of the present invention, even when the solid content concentration of the electrode mixture layer composition is higher than that of the conventional composition, it is possible to obtain a secondary battery that exhibits excellent cycle characteristics while ensuring coatability by reducing the viscosity of the electrode slurry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The composition for secondary battery electrode mixture layer of the present invention (hereinafter also referred to as "the composition") is in a slurry state that can be applied to a current collector. The secondary battery electrode of the present invention can be obtained by forming a mixture layer formed from the composition on the surface of a current collector such as copper foil or aluminum foil.

[0012] The composition will be described below together with the components constituting the composition, and the secondary battery electrode obtained by using the composition will be described in detail. In this specification, "(meth)acrylic" means acrylic and / or methacrylic, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl group" means acryloyl group and / or methacryloyl group.

[0013] The composition contains a binder, an active material, and water, and has a solid content of 40 mass% or more. The binder contains a crosslinked polymer having a carboxyl group and a non-crosslinked polymer having a structural unit derived from an ethylenically unsaturated carboxylic acid monomer.

[0014] 1. Crosslinked polymers with carboxyl groups <Structural Unit Derived from Ethylenically Unsaturated Carboxylic Acid Monomer> The crosslinked polymer having a carboxyl group contained in the binder (hereinafter also referred to as "the crosslinked polymer") may have a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "component (a1)"). When the crosslinked polymer has a carboxyl group due to the presence of such a structural unit, the adhesion to the current collector is improved, and the desolvation effect of lithium ions and ion conductivity are excellent, so that an electrode having low resistance and excellent high-rate characteristics can be obtained. In addition, water swelling is imparted, so that the dispersion stability of the active material and the like in the composition for the electrode mixture layer can be improved. The (a1) component can be introduced into the polymer by, for example, polymerizing a monomer containing an ethylenically unsaturated carboxylic acid monomer. Alternatively, it can be obtained by (co)polymerizing a (meth)acrylic acid ester monomer and then hydrolyzing it. Alternatively, it can be obtained by polymerizing (meth)acrylamide and (meth)acrylonitrile, etc., and then treating them with a strong alkali, or by reacting a polymer having a hydroxyl group with an acid anhydride.

[0015] Examples of the ethylenically unsaturated carboxylic acid monomer include (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, and fumaric acid; (meth)acrylamidoalkyl carboxylic acids such as (meth)acrylamidohexanoic acid and (meth)acrylamidododecanoic acid; ethylenically unsaturated monomers having a carboxyl group such as monohydroxyethyl succinate (meth)acrylate, ω-carboxy-caprolactone mono(meth)acrylate, and β-carboxyethyl (meth)acrylate, or their (partial) alkali neutralization products. One of these may be used alone, or two or more may be used in combination. Among the above, a compound having an acryloyl group as a polymerizable functional group is preferred, in that a polymer with a long primary chain length is obtained due to a high polymerization rate, and the binding strength of the binder is good, and acrylic acid is particularly preferred. When acrylic acid is used as the ethylenically unsaturated carboxylic acid monomer, a polymer with a high carboxyl group content can be obtained.

[0016] The content of the (a1) component in the present crosslinked polymer is not particularly limited, but may be, for example, 10% by mass or more and 100% by mass or less based on the total structural units of the present crosslinked polymer. By containing the (a1) component in such a range, excellent adhesion to the current collector can be easily ensured. The lower limit is, for example, 20% by mass or more, for example, 30% by mass or more, and for example, 40% by mass or more. When the lower limit is 50% by mass or more, the dispersion stability of the present composition becomes good and a higher binding force can be obtained, which is preferable, and may be 60% by mass or more, 70% by mass or more, or 80% by mass or more. The upper limit is, for example, 99.9% by mass or less, for example, 99.5% by mass or less, for example, 99% by mass or less, for example, 98% by mass or less, for example, 95% by mass or less, for example, 90% by mass or less, and for example, 80% by mass or less. The range can be an appropriate combination of these lower and upper limits, and can be, for example, 10% by mass or more and 100% by mass or less, for example, 50% by mass or more and 100% by mass or less, for example, 50% by mass or more and 99.9% by mass or less, for example, 50% by mass or more and 99% by mass or less, or for example, 50% by mass or more and 98% by mass or less.

[0017] <Other structural units> In addition to the component (a1), the crosslinked polymer may contain a structural unit derived from another ethylenically unsaturated monomer copolymerizable therewith (hereinafter also referred to as "component (b1)"). Examples of the component (b1) include structural units derived from an ethylenically unsaturated monomer compound having an anionic group other than a carboxyl group, such as a sulfonic acid group and a phosphoric acid group, or a nonionic ethylenically unsaturated monomer. These structural units can be introduced by copolymerizing a monomer containing an ethylenically unsaturated monomer compound having an anionic group other than a carboxyl group, such as a sulfonic acid group and a phosphoric acid group, or a nonionic ethylenically unsaturated monomer.

[0018] The ratio of the (b1) component to the total structural units of the crosslinked polymer can be 0% by mass or more and 90% by mass or less. The ratio of the (b1) component may be 1% by mass or more and 60% by mass or less, 2% by mass or more and 50% by mass or less, 5% by mass or more and 40% by mass or less, or 10% by mass or more and 30% by mass or less. In addition, when the (b1) component is contained at 1% by mass or more to the total structural units of the crosslinked polymer, the affinity to the electrolyte is improved, and therefore the effect of improving lithium ion conductivity can also be expected.

[0019] As the (b1) component, among those mentioned above, from the viewpoint of obtaining an electrode having good bending resistance, a structural unit derived from a nonionic ethylenically unsaturated monomer is preferred. Examples of the nonionic ethylenically unsaturated monomer include (meth)acrylamide and derivatives thereof, nitrile group-containing ethylenically unsaturated monomers, alicyclic structure-containing ethylenically unsaturated monomers, and hydroxyl group-containing ethylenically unsaturated monomers.

[0020] Examples of (meth)acrylamide derivatives include N-alkyl (meth)acrylamide compounds such as isopropyl (meth)acrylamide and t-butyl (meth)acrylamide; N-alkoxyalkyl (meth)acrylamide compounds such as Nn-butoxymethyl (meth)acrylamide and N-isobutoxymethyl (meth)acrylamide; and N,N-dialkyl (meth)acrylamide compounds such as dimethyl (meth)acrylamide and diethyl (meth)acrylamide. One of these may be used alone, or two or more may be used in combination.

[0021] Examples of the nitrile group-containing ethylenically unsaturated monomer include (meth)acrylonitrile; (meth)acrylic acid cyanoalkyl ester compounds such as (meth)acrylic acid cyanomethyl and (meth)acrylic acid cyanoethyl; cyano group-containing unsaturated aromatic compounds such as 4-cyanostyrene and 4-cyano-α-methylstyrene; vinylidene cyanide; and the like. One of these may be used alone, or two or more may be used in combination. Among the above, acrylonitrile is preferred because of its high nitrile group content.

[0022] Examples of the alicyclic structure-containing ethylenically unsaturated monomer include cycloalkyl (meth)acrylates which may have an aliphatic substituent, such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, cyclodecyl (meth)acrylate, and cyclododecyl (meth)acrylate; isobornyl (meth)acrylate, adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and cycloalkyl polyalcohol mono(meth)acrylates such as cyclohexanedimethanol mono(meth)acrylate and cyclodecanedimethanol mono(meth)acrylate. One of these may be used alone, or two or more may be used in combination.

[0023] Examples of the hydroxyl group-containing ethylenically unsaturated monomer include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate. One of these may be used alone, or two or more of them may be used in combination.

[0024] In terms of excellent binder binding properties, the crosslinked polymer or its salt preferably contains structural units derived from (meth)acrylamide and its derivatives, as well as nitrile group-containing ethylenically unsaturated monomers, alicyclic structure-containing ethylenically unsaturated monomers, etc. In addition, when a structural unit derived from a hydrophobic ethylenically unsaturated monomer having a solubility in water of 1 g / 100 ml or less is introduced as component (c), it can exhibit strong interaction with the electrode material and exhibit good binding properties to the active material. This allows a firm and well-integrated electrode mixture layer to be obtained, so that the above-mentioned "hydrophobic ethylenically unsaturated monomer having a solubility in water of 1 g / 100 ml or less" is particularly preferably an alicyclic structure-containing ethylenically unsaturated monomer.

[0025] In order to improve the cycle characteristics of the resulting secondary battery, the present crosslinked polymer or a salt thereof preferably contains a structural unit derived from a hydroxyl group-containing ethylenically unsaturated monomer, and preferably contains the structural unit in an amount of 0.5 mass % or more and 70 mass % or less, more preferably 2.0 mass % or more and 50 mass % or less, and even more preferably 10.0 mass % or more and 50 mass % or less.

[0026] As other nonionic ethylenically unsaturated monomers, for example, (meth)acrylic acid esters may be used. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl ester compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; Aromatic (meth)acrylic acid ester compounds such as phenyl (meth)acrylate, phenylmethyl (meth)acrylate, and phenylethyl (meth)acrylate; Examples of the alkoxyalkyl (meth)acrylate compounds include 2-methoxyethyl (meth)acrylate and 2-ethoxyethyl (meth)acrylate. One of these may be used alone, or two or more of them may be used in combination.

[0027] From the viewpoint of adhesion to the active material and cycle characteristics, aromatic (meth)acrylic acid ester compounds can be preferably used. From the viewpoint of further improving lithium ion conductivity and high rate characteristics, compounds having an ether bond, such as (meth)acrylic acid alkoxyalkyl esters such as 2-methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, are preferred, and 2-methoxyethyl (meth)acrylate is more preferred.

[0028] Among nonionic ethylenically unsaturated monomers, compounds having an acryloyl group are preferred because they have a fast polymerization rate, resulting in a polymer with a long primary chain length, and because they provide good binding strength for the binder. As nonionic ethylenically unsaturated monomers, compounds having a homopolymer glass transition temperature (Tg) of 0° C. or less are preferred because they provide good bending resistance for the resulting electrodes.

[0029] The crosslinked polymer may be in the form of a salt in which a part or all of the carboxyl groups contained in the polymer are neutralized. The type of salt is not particularly limited, and examples thereof include alkali metal salts such as lithium salts, sodium salts, and potassium salts; alkaline earth metal salts such as magnesium salts, calcium salts, and barium salts; other metal salts such as aluminum salts; ammonium salts, and organic amine salts. Among these, alkali metal salts and alkaline earth metal salts are preferred from the viewpoint of less adverse effects on battery characteristics, and alkali metal salts are more preferred.

[0030] The present crosslinked polymer is a crosslinked polymer having a crosslinked structure. The crosslinking method for the present crosslinked polymer is not particularly limited, and examples thereof include the following methods. 1) Copolymerization of crosslinkable monomers 2) Utilizing chain transfer to polymer chains during radical polymerization 3) After synthesizing a polymer having a reactive functional group, a crosslinking agent is added as necessary to perform post-crosslinking. Since the present crosslinked polymer has a crosslinked structure, a binder containing the crosslinked polymer or a salt thereof can have excellent binding strength. Among the above, the method of copolymerizing a crosslinkable monomer is preferred because the operation is simple and the degree of crosslinking can be easily controlled.

[0031] <Cross-linking monomer> Examples of the crosslinkable monomer include polyfunctional polymerizable monomers having two or more polymerizable unsaturated groups, and monomers having a self-crosslinkable crosslinkable functional group such as a hydrolyzable silyl group.

[0032] The polyfunctional polymerizable monomer is a compound having two or more polymerizable functional groups such as (meth)acryloyl group, alkenyl group, etc. in the molecule, and examples thereof include polyfunctional (meth)acrylate compounds, polyfunctional alkenyl compounds, compounds having both (meth)acryloyl group and alkenyl group, etc. These compounds may be used alone or in combination of two or more. Among these, polyfunctional alkenyl compounds are preferred in that they are easy to obtain a uniform crosslinked structure, and polyfunctional allyl ether compounds having two or more allyl ether groups in the molecule are particularly preferred.

[0033] Examples of the polyfunctional (meth)acrylate compound include di(meth)acrylates of dihydric alcohols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate; tri(meth)acrylates of trihydric or higher polyhydric alcohols such as trimethylolpropane tri(meth)acrylate, tri(meth)acrylate of an ethylene oxide modified trimethylolpropane, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and poly(meth)acrylates such as tetra(meth)acrylate; and bisamides such as methylene bisacrylamide and hydroxyethylene bisacrylamide.

[0034] Examples of polyfunctional alkenyl compounds include polyfunctional allyl ether compounds such as trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, tetraallyloxyethane, and polyallylsucrose; polyfunctional allyl compounds such as diallyl phthalate; and polyfunctional vinyl compounds such as divinylbenzene.

[0035] Examples of compounds having both a (meth)acryloyl group and an alkenyl group include allyl (meth)acrylate, isopropenyl (meth)acrylate, butenyl (meth)acrylate, pentenyl (meth)acrylate, and 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.

[0036] Specific examples of the monomer having a self-crosslinkable crosslinkable functional group include a hydrolyzable silyl group-containing vinyl monomer, N-methylol (meth)acrylamide, N-methoxyalkylacrylamide, etc. These compounds may be used alone or in combination of two or more.

[0037] The vinyl monomer containing hydrolyzable silyl group is not particularly limited as long as it is a vinyl monomer having at least one hydrolyzable silyl group.For example, vinyl silanes such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl methyl dimethoxysilane, vinyl dimethyl methoxysilane, etc.; silyl group-containing acrylic acid esters such as trimethoxysilylpropyl acrylate, triethoxysilylpropyl acrylate, methyl dimethoxysilylpropyl acrylate, etc.; silyl group-containing methacrylic acid esters such as trimethoxysilylpropyl methacrylate, triethoxysilylpropyl methacrylate, methyl dimethoxysilylpropyl methacrylate, dimethyl methoxysilylpropyl methacrylate, etc.; silyl group-containing vinyl ethers such as trimethoxysilylpropyl vinyl ether, etc.; silyl group-containing vinyl esters such as vinyl trimethoxysilyl undecanoate, etc.

[0038] When the present crosslinked polymer is crosslinked by a crosslinkable monomer, the amount of the crosslinkable monomer used is preferably 0.05 parts by mass or more and 5.0 parts by mass or less, more preferably 0.1 parts by mass or more and 5.0 parts by mass or less, even more preferably 0.2 parts by mass or more and 4.0 parts by mass or less, and even more preferably 0.3 parts by mass or more and 3.0 parts by mass or less, based on 100 parts by mass of the total amount of monomers other than the crosslinkable monomer (non-crosslinkable monomers). If the amount of the crosslinkable monomer used is 0.05 parts by mass or more, it is preferable in that the binding property and the stability of the mixture layer slurry are better. If it is 5.0 parts by mass or less, the stability of the polymer tends to be higher. Similarly, the amount of the crosslinkable monomer used is preferably 0.02 to 1.7 mol %, and more preferably 0.10 to 1.0 mol %, based on the total amount of monomers other than the crosslinkable monomer (non-crosslinkable monomers).

[0039] <Particle size of the crosslinked polymer> In the present composition, it is preferable that the present crosslinked polymer is not present as large lumps (secondary aggregates) but is well dispersed as water-swellable particles having an appropriate particle size, because this allows the binder containing the crosslinked polymer to exhibit good binding performance.

[0040] The crosslinked polymer preferably has a particle size (water-swollen particle size) in the volume-based median size range of 0.1 μm or more and 10.0 μm or less when the crosslinked polymer has a neutralization degree of 70 to 100 mol% based on the carboxyl group and is dispersed in water. The particle size is more preferably in the range of 0.1 μm or more and 8.0 μm or less, even more preferably in the range of 0.1 μm or more and 7.0 μm or less, even more preferably in the range of 0.2 μm or more and 5.0 μm or less, and even more preferably in the range of 0.5 μm or more and 3.0 μm or less. If the particle size is in the range of 0.1 μm or more and 10.0 μm or less, the particles are present in the composition at a suitable size and uniformly, so that the composition is highly stable and can exhibit excellent binding properties. If the particle size is more than 10.0 μm or less, there is a risk of insufficient binding properties as described above. In addition, there is a risk of insufficient coatability in that it is difficult to obtain a smooth coating surface. On the other hand, if the particle size is less than 0.1 μm, there are concerns from the viewpoint of stable production.

[0041] The particle size of the crosslinked polymer when dried (dry particle size) is preferably in the range of 0.03 μm to 3 μm in volumetric median size, more preferably 0.1 μm to 1 μm, and even more preferably 0.3 μm to 0.8 μm.

[0042] In the present crosslinked polymer, acid groups such as carboxyl groups derived from ethylenically unsaturated carboxylic acid monomers are neutralized so that the degree of neutralization in the present composition is 20 mol% or more, and it is preferable to use it as a salt. The degree of neutralization is more preferably 50 mol% or more, even more preferably 70 mol% or more, even more preferably 75 mol% or more, even more preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit of the degree of neutralization is 100 mol%, or it may be 98 mol% or 95 mol%. The range of the degree of neutralization can be appropriately combined with the above lower limit and upper limit, and may be, for example, 50 mol% or more and 100 mol% or less, 75 mol% or more and 100 mol% or less, or 80 mol% or more and 100 mol% or less. When the degree of neutralization is 20 mol% or more, it is preferable in that the water swelling property is good and the dispersion stabilization effect is easily obtained. In this specification, the neutralization degree can be calculated from the amount of a monomer having an acid group such as a carboxyl group and a neutralizing agent used for neutralization. The neutralization degree can be confirmed by measuring the powder of the crosslinked polymer or its salt after drying treatment at 80°C for 3 hours under reduced pressure conditions using IR, and by the intensity ratio of the peak derived from the C=O group of the carboxylic acid to the peak derived from the C=O group of the carboxylate.

[0043] <Method of Manufacturing the Crosslinked Polymer> The present crosslinked polymer can be prepared by known polymerization methods such as solution polymerization, precipitation polymerization, suspension polymerization, and emulsion polymerization, but precipitation polymerization and suspension polymerization (reverse phase suspension polymerization) are preferred from the viewpoint of productivity. Heterogeneous polymerization methods such as precipitation polymerization, suspension polymerization, and emulsion polymerization are preferred from the viewpoint of obtaining better performance in terms of binding property, etc., and among them, precipitation polymerization is more preferred. Precipitation polymerization is a method for producing polymers by carrying out a polymerization reaction in a solvent that dissolves the raw material unsaturated monomers but does not substantially dissolve the resulting polymer. As the polymerization proceeds, the polymer particles become larger through aggregation and growth, and a dispersion of polymer particles is obtained in which primary particles of tens to hundreds of nm are secondary aggregated to several μm to several tens of μm. A dispersion stabilizer can also be used to control the particle size of the polymer. The secondary aggregation can be suppressed by selecting a dispersion stabilizer, a polymerization solvent, etc. In general, precipitation polymerization in which secondary aggregation is suppressed is also called dispersion polymerization.

[0044] In the case of precipitation polymerization, the polymerization solvent may be selected from water and various organic solvents, etc., taking into consideration the type of monomer to be used, etc. In order to obtain a polymer having a longer primary chain length, it is preferable to use a solvent having a small chain transfer constant.

[0045] Specific polymerization solvents include water-soluble solvents such as methanol, t-butyl alcohol, acetone, methyl ethyl ketone, acetonitrile, and tetrahydrofuran, as well as benzene, ethyl acetate, dichloroethane, n-hexane, cyclohexane, and n-heptane, and these can be used alone or in combination of two or more. Alternatively, these can be used as a mixed solvent with water. In the present invention, the water-soluble solvent refers to a solvent having a solubility in water of more than 10 g / 100 ml at 20° C. Of the above, methyl ethyl ketone and acetonitrile are preferred because they have good polymerization stability with little generation of coarse particles and little adhesion to the reactor, the precipitated polymer fine particles are not prone to secondary aggregation (or even if secondary aggregation does occur, it is easily disintegrated in an aqueous medium), they give polymers with small chain transfer constants and large degrees of polymerization (primary chain lengths), and they are easy to handle during the neutralization step described below.

[0046] The polymerization initiator may be any known polymerization initiator such as an azo compound, an organic peroxide, or an inorganic peroxide, but is not particularly limited. The conditions of use may be adjusted so that an appropriate amount of radicals is generated by known methods such as thermal initiation, redox initiation using a reducing agent, or UV initiation. In order to obtain a crosslinked polymer with a long primary chain length, it is preferable to set the conditions so that the amount of radicals generated is as small as possible within the allowable range of production time.

[0047] The amount of the polymerization initiator used is preferably, for example, 0.001 to 2 parts by mass, for example, 0.005 to 1 part by mass, or for example, 0.01 to 0.1 part by mass, when the total amount of the monomer components used is 100 parts by mass. If the amount of the polymerization initiator used is 0.001 part by mass or more, the polymerization reaction can be stably carried out, and if it is 2 parts by mass or less, a polymer having a long primary chain length is easily obtained.

[0048] The polymerization temperature varies depending on conditions such as the type and concentration of the monomers used, but is preferably 0 to 100° C., more preferably 20 to 80° C. The polymerization temperature may be constant or may vary during the polymerization reaction. The polymerization time is preferably 1 minute to 20 hours, more preferably 1 hour to 10 hours.

[0049] 2. Non-crosslinked polymer having structural units derived from ethylenically unsaturated carboxylic acid monomers The composition contains, as a binder, a non-crosslinked polymer having a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "the non-crosslinked polymer"). The non-crosslinked polymer has a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (hereinafter also referred to as "component (a2)"). The component (a2) and the method of introducing it are the same as those described for the component (a1) of the crosslinked polymer.

[0050] The content of the (a2) component in the present non-crosslinked polymer is not particularly limited, but in terms of solubility in water, it is preferably 50% by mass or more and 100% by mass or less, more preferably 60% by mass or more and 100% by mass or less, even more preferably 70% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, based on all structural units of the present non-crosslinked polymer.

[0051] <Other structural units> In addition to the component (a2), the present non-crosslinked polymer may contain a structural unit derived from another ethylenically unsaturated monomer copolymerizable therewith (hereinafter also referred to as "component (b2)"). The component (b2) and the method for introducing it are the same as those described for the component (b1) of the present crosslinked polymer. The proportion of the (b2) component can be 0% by mass or more and 50% by mass or less, or may be 1% by mass or more and 40% by mass or less, or 2% by mass or more and 30% by mass or less, or 5% by mass or more and 20% by mass or less, based on all structural units of the non-crosslinked polymer.

[0052] The non-crosslinked polymer may be in the form of a salt in which a part or all of the carboxyl groups contained in the polymer are neutralized. The type of salt is not particularly limited, and examples thereof include alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as calcium salts and barium salts; other metal salts such as magnesium salts and aluminum salts; ammonium salts and organic amine salts. Among these, alkali metal salts and magnesium salts are preferred from the viewpoint of less adverse effects on battery characteristics, and alkali metal salts are more preferred.

[0053] In the present non-crosslinked polymer, acid groups such as carboxyl groups derived from ethylenically unsaturated carboxylic acid monomers are neutralized so that the degree of neutralization in the present composition is 20 mol% or more, and it is preferable to use it as a salt. The degree of neutralization is more preferably 50 mol% or more, even more preferably 70 mol% or more, even more preferably 75 mol% or more, even more preferably 80 mol% or more, and particularly preferably 85 mol% or more. The upper limit of the degree of neutralization is 100 mol%, and may be 98 mol% or 95 mol%. The range of the degree of neutralization can be appropriately combined with the above lower limit and upper limit, and may be, for example, 50 mol% or more and 100 mol% or less, 75 mol% or more and 100 mol% or less, or 80 mol% or more and 100 mol% or less. When the degree of neutralization is 20 mol% or more, it is preferable in that solubility in water is easily ensured. In this specification, the degree of neutralization can be calculated by calculation from the charged amount of a monomer having an acid group such as a carboxyl group and a neutralizing agent used for neutralization. The degree of neutralization can be confirmed by subjecting the crosslinked polymer or its salt to IR measurement of the powder after drying treatment at 80°C under reduced pressure conditions for 3 hours, and checking the intensity ratio of the peak derived from the C=O group of the carboxylic acid to the peak derived from the C=O group of the carboxylate.

[0054] The weight average molecular weight (Mw) of the non-crosslinked polymer is not particularly limited, but is preferably 5,000 or more, more preferably 10,000 or more, in terms of obtaining an electrode mixture layer with excellent binding properties. Mw may be 100,000 or more, 500,000 or more, or 1,000,000 or more. The upper limit of Mw is not particularly limited, but may be, for example, 10,000,000 or less, or 5,000,000 or less, in terms of handling during production.

[0055] The binder used in the composition includes the present crosslinked polymer and the present non-crosslinked polymer. The amount of the present non-crosslinked polymer used is 7.5 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of the total amount of the crosslinked polymer. The amount of the non-crosslinked polymer used may be 15 parts by mass or more, 25 parts by mass or more, 35 parts by mass or more, or 45 parts by mass or more. The upper limit may be 190 parts by mass or less, 180 parts by mass or less, 170 parts by mass or less, or 160 parts by mass or less. The range may be a range that appropriately combines such lower and upper limits, and may be, for example, 15 parts by mass or more and 190 parts by mass or less, for example, 25 parts by mass or more and 180 parts by mass or less, or for example, 35 parts by mass or more and 170 parts by mass or less, or for example, 35 parts by mass or more and 160 parts by mass or less.

[0056] In this way, by using a specific amount of the present non-crosslinked polymer in combination with the present crosslinked polymer, it is possible to obtain a secondary battery that exhibits excellent cycle characteristics while ensuring coatability by reducing the viscosity of the electrode slurry when the solid content concentration of the electrode mixture layer composition is higher than that of the conventional one. If the amount of the present non-crosslinked polymer used is 7.5 parts by mass or more, the effect can be achieved. In addition, if the amount of the present non-crosslinked polymer used exceeds 200 parts by mass, sufficient coatability may not be obtained.

[0057] <Method of producing the present non-crosslinked polymer> The present non-crosslinked polymer can be prepared by using a known polymerization method such as solution polymerization, precipitation polymerization, suspension polymerization, or emulsion polymerization, and the polymerization method may be appropriately selected depending on the molecular weight, composition, and the like.

[0058] The polymerization initiator may be any known polymerization initiator such as an azo compound, an organic peroxide, an inorganic peroxide, etc., but is not particularly limited. The conditions of use can be adjusted so that an appropriate amount of radicals is generated by a known method such as thermal initiation, redox initiation using a reducing agent, UV initiation, etc. For the purpose of adjusting the molecular weight, etc., a known chain transfer agent may be used as necessary.

[0059] 3. Composition for secondary battery electrode mixture layer The composition for a secondary battery electrode mixture layer of the present invention contains a binder, an active material, and water. The amount of the binder used in the present composition is, for example, 0.1 parts by mass or more and 20 parts by mass or less, based on 100 parts by mass of the total amount of the active material. The amount used is, for example, 0.2 parts by mass or more and 10 parts by mass or less, for example, 0.3 parts by mass or more and 8 parts by mass or less, and for example, 0.4 parts by mass or more and 5 parts by mass or less. If the amount of the binder used is 0.1 parts by mass or more, sufficient binding property can be obtained. In addition, the dispersion stability of the active material and the like can be ensured, and a uniform mixture layer can be formed. If the amount of the binder used is 20 parts by mass or less, the present composition does not become highly viscous, and the coatability to the current collector can be ensured. As a result, a mixture layer having a uniform and smooth surface can be formed.

[0060] Among the above-mentioned active materials, lithium salts of transition metal oxides can be used as the positive electrode active material. For example, layered rock salt type and spinel type lithium-containing metal oxides can be used. Specific compounds of layered rock salt type positive electrode active materials include lithium cobalt oxide, lithium nickel oxide, and NCM{Li(Ni x ,Co y ,Mn z ), x+y+z=1} and NCA{Li(Ni 1-a-b Co a Alb )}, etc. Examples of the spinel-type positive electrode active material include lithium manganate, etc. In addition to oxides, phosphates, silicates, sulfur, etc. are used, and examples of the phosphates include olivine-type lithium iron phosphate, etc. As the positive electrode active material, one of the above may be used alone, or two or more may be combined to be used as a mixture or composite.

[0061] In addition, when a positive electrode active material containing a layered rock salt type lithium-containing metal oxide is dispersed in water, the lithium ions on the active material surface are exchanged with hydrogen ions in the water, and the dispersion liquid becomes alkaline. For this reason, there is a risk that aluminum foil (Al), which is a common positive electrode current collector material, may be corroded. In such a case, it is preferable to neutralize the alkali content eluted from the active material by using the unneutralized or partially neutralized present crosslinked polymer as a binder. In addition, it is preferable to use the unneutralized or partially neutralized present crosslinked polymer in an amount such that the amount of unneutralized carboxyl groups in the present crosslinked polymer is equivalent to or greater than the amount of alkali eluted from the active material.

[0062] Since all positive electrode active materials have low electrical conductivity, they are generally used with the addition of a conductive assistant. Examples of the conductive assistant include carbon-based materials such as carbon black, carbon nanotubes, carbon fiber, graphite powder, and carbon fiber. Of these, carbon black, carbon nanotubes, and carbon fiber are preferred because they are easy to obtain excellent electrical conductivity. As carbon black, ketjen black and acetylene black are preferred. The conductive assistant may be one of the above alone or two or more may be used in combination. The amount of the conductive assistant may be, for example, 0.2 to 20 parts by mass, or, for example, 0.2 to 10 parts by mass, based on 100 parts by mass of the total amount of the active material, from the viewpoint of achieving both electrical conductivity and energy density. The positive electrode active material may be surface-coated with a carbon-based material having electrical conductivity.

[0063] On the other hand, examples of the negative electrode active material include carbon-based materials, lithium metal, lithium alloys, and metal oxides, and one or more of these can be used in combination. Among these, active materials made of carbon-based materials such as natural graphite, artificial graphite, hard carbon, and soft carbon (hereinafter also referred to as "carbon-based active materials") are preferred, and graphite such as natural graphite and artificial graphite, and hard carbon are more preferred. In the case of graphite, spherical graphite is preferably used from the viewpoint of battery performance, and the preferred range of the particle size is, for example, 1 to 20 μm, and also, for example, 5 to 15 μm. In order to increase the energy density, metals or metal oxides capable of occluding lithium, such as silicon and tin, can also be used as the negative electrode active material. Among them, silicon has a higher capacity than graphite, and active materials made of silicon-based materials such as silicon, silicon alloys, and silicon oxides such as silicon monoxide (SiO) (hereinafter also referred to as "silicon-based active materials") can be used. However, while the silicon-based active material has a high capacity, it undergoes a large volume change during charging and discharging. For this reason, it is preferable to use it in combination with the carbon-based active material. In this case, if the amount of silicon-based active material is large, the electrode material may collapse, and the cycle characteristics (durability) may be significantly reduced. From this point of view, when the silicon-based active material is used in combination, the amount of the silicon-based active material is, for example, 60% by mass or less, or, for example, 30% by mass or less, relative to the carbon-based active material.

[0064] Since the carbon-based active material itself has good electrical conductivity, it is not necessary to add a conductive additive. When a conductive additive is added for the purpose of further reducing resistance, etc., the amount of the conductive additive used is, for example, 10 parts by mass or less, or, for example, 5 parts by mass or less, based on 100 parts by mass of the total amount of the active material, from the viewpoint of energy density.

[0065] When the composition is in a slurry state, the amount of the active material used is, for example, in the range of 10 to 75 mass %, or, for example, in the range of 30 to 65 mass %, based on the total amount of the composition. If the amount of the active material used is 10 mass % or more, migration of the binder, etc. is suppressed, and it is also advantageous in terms of the drying cost of the medium. On the other hand, if it is 75 mass % or less, the fluidity and coatability of the composition can be ensured, and a uniform mixture layer can be formed.

[0066] The composition uses water as a medium. In order to adjust the properties and drying property of the composition, the composition may be mixed with lower alcohols such as methanol and ethanol, carbonates such as ethylene carbonate, ketones such as acetone, tetrahydrofuran, N-methylpyrrolidone, and other water-soluble organic solvents. The proportion of water in the mixed medium is, for example, 50% by mass or more, and, for example, 70% by mass or more.

[0067] When the present composition is made into a coatable slurry state, the content of the water-containing medium in the entire composition can be in the range of, for example, 25 to 60 mass %, and can be, for example, 35 to 60 mass %, from the viewpoints of the coatability of the slurry, the energy cost required for drying, and productivity.

[0068] The composition may further use other binder components such as styrene butadiene rubber (SBR) latex, carboxymethyl cellulose (CMC), acrylic latex, and polyvinylidene fluoride latex. When other binder components are used in combination, the amount of the binder components used may be, for example, 0.1 to 5 parts by mass or less, or, for example, 0.1 to 2 parts by mass or less, or, for example, 0.1 to 1 part by mass or less, based on 100 parts by mass of the total amount of the active material. If the amount of the other binder components used exceeds 5% by mass, the resistance increases, and the high-rate characteristics may become insufficient. Among the above, SBR latex and CMC are preferred in terms of excellent balance between binding property and flex resistance, and it is more preferred to use SBR latex and CMC in combination.

[0069] The SBR latex refers to an aqueous dispersion of a copolymer having a structural unit derived from an aromatic vinyl monomer such as styrene and a structural unit derived from an aliphatic conjugated diene monomer such as 1,3-butadiene. Examples of the aromatic vinyl monomer include α-methylstyrene, vinyltoluene, divinylbenzene, and the like, in addition to styrene, and one or more of these can be used. The structural unit derived from the aromatic vinyl monomer in the copolymer can be, for example, in the range of 20 to 70% by mass, or, for example, in the range of 30 to 60% by mass, mainly from the viewpoint of binding property. Examples of the aliphatic conjugated diene monomer include 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, and the like, in addition to 1,3-butadiene, and one or more of these can be used. The structural unit derived from the aliphatic conjugated diene monomer in the copolymer can be, for example, in the range of 30 to 70 mass %, or, for example, in the range of 40 to 60 mass %, in order to improve the binding property of the binder and the flexibility of the obtained electrode. In addition to the above-mentioned monomers, the styrene / butadiene-based latex may use other monomers as copolymerization monomers, such as nitrile group-containing monomers such as (meth)acrylonitrile, carboxyl group-containing monomers such as (meth)acrylic acid, itanconic acid, maleic acid, and ester group-containing monomers such as methyl (meth)acrylate, in order to further improve performance such as binding property. The structural units derived from the other monomers in the copolymer can be in the range of, for example, 0 to 30% by mass, and can be in the range of, for example, 0 to 20% by mass.

[0070] The CMC refers to a nonionic cellulose-based semisynthetic polymer compound substituted with a carboxymethyl group and its salt. Examples of the nonionic cellulose-based semisynthetic polymer compound include alkyl celluloses such as methyl cellulose, methyl ethyl cellulose, ethyl cellulose, and microcrystalline cellulose; Examples of the hydroxyalkyl cellulose include hydroxyethyl cellulose, hydroxybutyl methyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose stearoxy ether, carboxymethyl hydroxyethyl cellulose, alkyl hydroxyethyl cellulose, and nonoxynyl hydroxyethyl cellulose.

[0071] The composition for secondary battery electrode mixture layer of the present invention is essentially composed of the active material, water and binder, and is obtained by mixing each component using a known means. The method of mixing each component is not particularly limited, and a known method can be adopted, but a method of dry blending powder components such as active material, conductive assistant and binder, and then mixing with a dispersion medium such as water and dispersing and kneading is preferred. When the composition is obtained in a slurry state, it is preferable to finish the slurry without poor dispersion or aggregation. As a mixing means, known mixers such as a planetary mixer, a thin film swirling mixer and a self-revolving mixer can be used, but it is preferable to use a thin film swirling mixer in that a good dispersion state can be obtained in a short time. In addition, when using a thin film swirling mixer, it is preferable to perform preliminary dispersion in advance with a stirrer such as a disperser. The viscosity of the slurry is not particularly limited as long as the effects of the present invention are achieved, but the viscosity can be, for example, in the range of 100 to 5,000 mPa·s, or, for example, in the range of 500 to 4,500 mPa·s, or, for example, in the range of 1,000 to 3,000 mPa·s, as Brookfield viscosity (25°C) at 20 rpm. If the viscosity of the slurry is within the above range, good coatability can be ensured.

[0072] 4. Secondary battery electrode The secondary battery electrode of the present invention comprises a mixture layer formed from the composition for secondary battery electrode mixture layer of the present invention on the surface of a current collector such as copper or aluminum. The mixture layer is formed by applying the composition to the surface of the current collector and then drying and removing the medium such as water. The method for applying the composition is not particularly limited, and known methods such as doctor blade method, dip method, roll coating method, comma coating method, curtain coating method, gravure coating method, and extrusion method can be adopted. In addition, the drying can be performed by known methods such as hot air blowing, reduced pressure, (far) infrared radiation, and microwave irradiation. Usually, the mixture layer obtained after drying is subjected to a compression treatment using a mold press, a roll press, or the like. By compressing, the active material and the binder are brought into close contact with each other, and the strength of the mixture layer and its adhesion to the current collector can be improved. By compressing, the thickness of the mixture layer can be adjusted to, for example, about 30 to 80% of the thickness before compression, and the thickness of the mixture layer after compression is generally about 4 to 200 μm.

[0073] 5. Secondary battery A secondary battery can be produced by providing the secondary battery electrode of the present invention with a separator and an electrolyte. The electrolyte may be in a liquid state or a gel state. The separator is disposed between the positive and negative electrodes of the battery, and serves to prevent short circuits caused by contact between the electrodes and to retain the electrolyte to ensure ionic conductivity. The separator is preferably a film-like insulating microporous membrane having good ion permeability and mechanical strength. Specific examples of the material that can be used include polyolefins such as polyethylene and polypropylene, and polytetrafluoroethylene.

[0074] The electrolyte may be any known electrolyte that is generally used depending on the type of active material. In lithium-ion secondary batteries, specific solvents include cyclic carbonates with high dielectric constants and high electrolyte dissolving ability, such as propylene carbonate and ethylene carbonate, and chain carbonates with low viscosity, such as ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate, which may be used alone or as a mixed solvent. The electrolyte is used by dissolving lithium salts, such as LiPF6, LiSbF6, LiBF4, LiClO4, and LiAlO4, in these solvents. In nickel-hydrogen secondary batteries, an aqueous potassium hydroxide solution may be used as the electrolyte. A secondary battery is obtained by storing a positive electrode plate and a negative electrode plate separated by a separator in a spiral or stacked structure in a case or the like.

[0075] As described above, a secondary battery having an electrode provided with a mixture layer formed from the composition for a secondary battery electrode mixture layer disclosed in the present specification exhibits good durability (cycle characteristics) even after repeated charging and discharging, and is therefore suitable for use as an in-vehicle secondary battery, etc. EXAMPLES

[0076] The present invention will be specifically described below based on examples. Note that the present invention is not limited to these examples. Note that, in the following, "parts" and "%" mean parts by mass and % by mass unless otherwise specified.

[0077] (Viscosity measurement of 2% by weight aqueous solution of this crosslinked polymer) The crosslinked polymer having a carboxyl group obtained in each of the following manufacturing examples was dissolved in deionized water to prepare an aqueous solution having a concentration of 2% by mass. The temperature of the aqueous solution was adjusted to 25° C.±1° C., and the viscosity of the aqueous solution having a concentration of 2% by mass was measured using a B-type viscometer at 12 rpm.

[0078] (Measurement of electrode slurry viscosity) The electrode slurries obtained in the following respective Examples and Comparative Examples were adjusted to 25° C.±1° C., and then the slurry viscosities were measured using a Brookfield viscometer at 20 rpm.

[0079] <Production of the present crosslinked polymer salt> (Production Example 1: Production of Carboxyl Group-Containing Crosslinked Polymer Salt R-1) For the polymerization, a reactor equipped with a stirring blade, a thermometer, a reflux condenser and a nitrogen inlet tube was used. Into the reactor, 567 parts of acetonitrile, 2.20 parts of ion-exchanged water, 100.0 parts of acrylic acid (hereinafter referred to as "AA"), 0.90 parts of trimethylolpropane diallyl ether (manufactured by Daiso Co., Ltd., trade name "Neoallyl T-20"), and 1.0 mol% of triethylamine relative to the AA were charged. After the inside of the reactor was sufficiently replaced with nitrogen, the inside temperature was raised to 55°C by heating. After confirming that the inside temperature was stable at 55°C, 0.040 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., trade name "V-65") was added as a polymerization initiator, and the reaction liquid became cloudy, so this point was determined as the polymerization initiation point. The polymerization reaction was continued while maintaining the internal temperature at 55°C by adjusting the external temperature (water bath temperature), and cooling of the reaction solution was started 24 hours after the polymerization initiation point, and after the internal temperature had dropped to 25°C, 52.4 parts of lithium hydroxide monohydrate (hereinafter referred to as "LiOH·H2O") powder was added. After the addition, stirring was continued at room temperature for 12 hours, and a slurry-like polymerization reaction solution was obtained in which particles of carboxyl group-containing crosslinked polymer salt R-1 (Li salt, neutralization degree 90 mol%) were dispersed in the medium.

[0080] The obtained polymerization reaction solution was centrifuged to settle the polymer particles, and the supernatant was removed. The precipitate was then redispersed in acetonitrile of the same weight as the polymerization reaction solution, and the polymer particles were precipitated by centrifugation to remove the supernatant. This washing operation was repeated twice. The precipitate was collected and dried at 80°C for 3 hours under reduced pressure conditions to remove the volatile matter, thereby obtaining a powder of carboxyl group-containing polymer salt R-1. Since the carboxyl group-containing crosslinked polymer salt R-1 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of the carboxyl group-containing polymer salt R-1 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O of the carboxylic acid Li, which was 90 mol%, equal to the calculated value from the charge.

[0081] (Production Examples 2 to 5: Production of Carboxyl Group-Containing Crosslinked Polymer Salts R-2 to R-5) The same operation as in Production Example 1 was carried out except that the amounts of the monomer, crosslinkable monomer, ion-exchanged water and neutralizing agent were as shown in Table 1, to obtain a polymerization reaction solution containing carboxyl group-containing crosslinked polymer salts R-2 to R-5. Next, the same operation as in Production Example 1 was carried out for each polymerization reaction liquid to obtain powdered carboxyl group-containing crosslinked polymer salts R-2 to R-5. Each carboxyl group-containing crosslinked polymer salt was stored in a sealed container having water vapor barrier properties.

[0082] [Table 1]

[0083] Details of the compounds used in Table 1 are shown below. AA: Acrylic acid HEA: 2-hydroxyethyl acrylate T-20: Trimethylolpropane diallyl ether (manufactured by Daiso Co., Ltd., product name "Neoallyl T-20") TEA: Triethylamine AcN: Acetonitrile

[0084] <Production of the present non-crosslinked polymer salt> (Production Examples 6 to 9: Production of the present non-crosslinked polymer salts R-6 to R-9) Details of the present non-crosslinked polymers R-6 to R-9 used in the Examples and Comparative Examples are shown below. R-6 to R-8 were prepared by adding powders of lithium hydroxide monohydrate (hereinafter referred to as "LiOH·H₂O") to the following unneutralized non-crosslinked polyacrylic acids so as to neutralize them at 100 mol%, respectively, and continuing stirring at room temperature for 12 hours after the addition. R-9 was prepared by performing the same operations as R-6 to R-8 except that LiOH·H₂O was added so as to neutralize it at 75 mol%. ·R-6: Lithium-neutralized salt of non-crosslinked polyacrylic acid. As the unneutralized non-crosslinked polyacrylic acid, the product name "Jumimer AC-10LHP" (manufactured by Toagosei Co., Ltd., Mw 1,500,000) was used. ·R-7: Lithium-neutralized salt of non-crosslinked polyacrylic acid. As the unneutralized non-crosslinked polyacrylic acid, the product name "Aron A-6801" (manufactured by Toagosei Co., Ltd., Mw 100,000) was used. ·R-8: Lithium-neutralized salt of non-crosslinked polyacrylic acid. As the unneutralized non-crosslinked polyacrylic acid, the product name "Aron A-10SL" (manufactured by Toagosei Co., Ltd., Mw 6,000) was used. ·R-9: Partially lithium-neutralized salt of non-crosslinked polyacrylic acid. As the unneutralized non-crosslinked polyacrylic acid, the product name "Jumimer AC-10LHP" (manufactured by Toagosei Co., Ltd., Mw 1,500,000) was used. Note that "Jumimer" and "Aron" are registered trademarks of Toagosei Co., Ltd.

[0085] Example 1 <Preparation of electrode mixture layer composition> A material in which carbon was coated on the surface of SiOx (0.8 < x < 1.2) by 10% by CVD method (hereinafter referred to as "Si-based active material") was prepared, and a mixture of graphite and the Si-based active material was used as the active material. As the binder, a mixture of the present crosslinked polymer salt R-1, the present non-crosslinked polymer salt R-6, styrene-butadiene rubber (SBR) latex, and carboxymethyl cellulose (CMC) was used. The electrode mixture layer composition was mixed for 2 hours using TK Hivismix manufactured by Primix Corp. in a mass ratio of graphite:Si-based active material:R-1:R-6:SBR:CMC=90:10:1.0:0.5:1.0:1.0 (solids) with water as a dilution solvent so that the solids concentration of the electrode mixture layer composition was 50 mass%. The electrode mixture layer composition in a slurry state (electrode slurry) was prepared by mixing for 2 hours using TK Hivismix manufactured by Primix Corp. The viscosity of the electrode slurry was 3,140 mPa s, which was a sufficiently low value. The obtained electrode slurry was used to prepare an electrode, which was then evaluated. The specific procedure and evaluation method are described below.

[0086] <Preparation of negative electrode plate> The electrode slurry was applied to both sides of a copper foil (thickness: 20 μm) and dried to form a mixture layer. After that, the mixture layer had a thickness of 27 μm and a packing density of 1.3 g / cm 3 After rolling to a thickness of 100 mm, the plate was punched out into a 3 cm square to obtain a negative electrode plate.

[0087] (Coatability) The coatability of the electrode slurry in the preparation of the negative electrode plate was evaluated based on the following criteria and was evaluated as "◯". (Evaluation Criteria) ◯: No abnormal appearance such as streaks or bumps was observed on the surface. △: Slight abnormalities in appearance such as streaks or bumps are observed on the surface. ×: Significant abnormalities in appearance such as streaks and bumps are observed on the surface.

[0088] <Preparation of positive electrode plate> In N-methylpyrrolidone (NMP) solvent, 100 parts of lithium iron phosphate (LFP) as a positive electrode active material, 0.2 parts of carbon nanotubes as a conductive agent, 2 parts of Ketjen black, and 0.6 parts of vapor grown carbon fiber (VGCF) were mixed and added, and polyvinylidene fluoride (PVDF) was mixed as a binder for the electrode composition to prepare a positive electrode composition. The positive electrode composition was applied to an aluminum current collector (thickness: 15 μm) and dried to form a mixture layer. Thereafter, the thickness of the mixture layer was 88 μm and the packing density was 3.1 g / cm. 3After rolling to a thickness of 100 mm, the mixture was punched out into a 3 cm square to obtain a positive electrode plate.

[0089] <Preparation of secondary battery> A laminated type lithium ion secondary battery was fabricated using the positive electrode plate, the negative electrode plate, and a separator. The electrolyte used was a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (DEC) in a volume ratio of 25:75, in which LiPF6 was dissolved at a concentration of 1.0 mol / L.

[0090] (Evaluation of cycle characteristics) The lithium ion secondary battery of the laminated cell prepared above was charged and discharged at a charge / discharge rate of 0.2 C under CC discharge conditions of 2.7 to 3.4 V, and the initial capacity C0 was measured. Furthermore, charging and discharging were repeated in an environment of 25°C, and the capacity C0 after 50 cycles was measured. 50 The cycle characteristic (ΔC) calculated by the following formula was 93.0%, and the cycle characteristic based on the following criteria was evaluated as "Good." Note that a higher ΔC value indicates better cycle characteristics. ΔC=C 50 / C0×100(%) (Evaluation Criteria) ◎: Charge / discharge capacity retention rate is 95.0% or more ○: Charge / discharge capacity retention rate is 90.0% or more but less than 95.0% △: Charge / discharge capacity retention rate is 85.0% or more but less than 90.0% ×: Charge / discharge capacity retention rate is less than 85.0%

[0091] Examples 2 to 10 and Comparative Examples 1 to 3 Except for the present crosslinked polymer salt and the present non-crosslinked polymer salt being as shown in Table 2, the same operation as in Example 1 was carried out to prepare an electrode slurry, and the slurry viscosity was measured. In addition, the coating property of the electrode slurry and the cycle characteristics of the secondary battery obtained using the same were evaluated. The results are shown in Table 2.

[0092] [Table 2]

[0093] <Evaluation Results> As is clear from the results of Examples 1 to 10, the compositions for secondary battery electrode mixture layers (electrode slurries) of the present invention all had good coatability, and the secondary batteries equipped with electrodes obtained using the compositions also had excellent cycle characteristics. In contrast, when the composition did not contain a non-crosslinked polymer having a structural unit derived from an ethylenically unsaturated carboxylic acid monomer (Comparative Example 1) or when the amount of the non-crosslinked polymer used was less than 7.5 parts by mass per 100 parts by mass of the total amount of the crosslinked polymer (Comparative Example 2), the cycle characteristics were significantly inferior, and when the amount of the non-crosslinked polymer used was more than 200 parts by mass per 100 parts by mass of the total amount of the crosslinked polymer (Comparative Example 3), the coatability was significantly inferior. [Industrial Applicability]

[0094] A secondary battery having an electrode obtained by using the composition for a secondary battery electrode mixture layer of the present invention exhibits good durability (cycle characteristics), and is therefore expected to be applied to a secondary battery for vehicle use. It is also useful for the use of an active material containing silicon, and is expected to contribute to the increase in the capacity of batteries. The composition for secondary battery electrode mixture layer of the present invention can be suitably used in particular for non-aqueous electrolyte secondary battery electrodes, and is particularly useful for non-aqueous electrolyte lithium ion secondary batteries having high energy density.

Claims

1. A composition for a secondary battery electrode mixture layer comprising a binder, an active material, and water, The solid content of the composition is 40% by mass or more, The binder includes a crosslinked polymer having a carboxyl group and a non-crosslinked polymer having a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, The composition for a secondary battery electrode mixture layer, wherein the amount of the non-crosslinked polymer used is 7.5 parts by mass or more and 200 parts by mass or less with respect to 100 parts by mass of a total amount of the crosslinked polymer.

2. The composition for a secondary battery electrode mixture layer according to claim 1, wherein the crosslinked polymer has 10 mass% or more and 100 mass% or less of structural units derived from ethylenically unsaturated carboxylic acid monomers relative to all structural units thereof.

3. The crosslinked polymer has 50% by mass or more and 100% by mass or less of structural units derived from an ethylenically unsaturated carboxylic acid monomer based on all structural units thereof, The composition for secondary battery electrode mixture layer according to claim 1 or 2, wherein the non-crosslinked polymer has 50% by mass or more and 100% by mass or less of structural units derived from an ethylenically unsaturated carboxylic acid monomer relative to all structural units thereof.

4. The composition for a secondary battery electrode mixture layer according to any one of claims 1 to 3, wherein the degree of neutralization of the crosslinked polymer is 70 mol % or more.

5. The composition for secondary battery electrode mixture layer according to any one of claims 1 to 4, wherein the crosslinked polymer is obtained by using a crosslinkable monomer, and the amount of the crosslinkable monomer used is 0.05 parts by mass or more and 5.0 parts by mass or less with respect to 100 parts by mass of a total amount of the non-crosslinkable monomers.

6. The composition for a secondary battery electrode mixture layer according to any one of claims 1 to 5, wherein the degree of neutralization of the non-crosslinked polymer is 70 mol % or more.

7. The secondary battery electrode mixture layer composition according to any one of claims 1 to 6, wherein the non-crosslinked polymer has a weight average molecular weight of 5,000 or more.

8. The secondary electrode mixture layer composition according to any one of claims 1 to 7, wherein the binder further comprises a styrene butadiene rubber (SBR)-based latex and / or carboxymethyl cellulose (CMC).

9. A secondary battery electrode comprising a mixture layer formed from the composition for secondary battery electrode mixture layer according to any one of claims 1 to 8 on a surface of a current collector.

10. A secondary battery comprising the secondary battery electrode according to claim 9.

Citation Information

Patent Citations

  • Aqueous binder

    JP2019157000A

  • Binder for lithium cell, composition for producing electrode, and electrode

    WO2014065407A1

  • Negative electrode substance for nonaqueous electrolyte secondary battery, negative electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    WO2016051811A1

  • Binder for nonaqueous electrolyte secondary cell electrode, method for producing binder, and use thereof

    WO2017073589A1

  • Binder for non-aqueous electrolyte secondary cell electrode

    WO2018180232A1